Palliative care research: using the delphi method - Tânia dos Santos Afonso; Lurdes Martins; Manuel Luís Capelas; Zaida Charepe (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2018)
Introduction: Due to the challenges that are increasingly complex in palliative care, the need to develop community health care raises. Aim: Understand the application of the Delphi method for research in palliative care. Materials and Methods: Started an integrative literature review using research on EBSCO host database. Results: The primary purpose of the eight articles selected is to create indicators for health evaluation. The Delphi method used in all the studies has in common, besides the intention to create new data in health care practice, the use to manage a high number of data from geographically distant points. Conclusion: Our literature research allowed us to conclude that there are still few studies using the Delphi method in palliative care. This instrument has excellent utility in the systematization, organization and evaluation of the contexts and care practices. We reinforce the importance of developing this resource in this context.